Anger, aggression and road rage behaviour in Malaysian drivers. (February 2015) - Sullman, Mark J.M.; Stephens, Amanda N.; Yong, Michelle
Highlights: The expression of driving anger was studied in Malaysian drivers. CFA supported the four factor structure of the 49-item DAX. Total Aggressive Expression (TAE) was significantly related to crash involvement. TAE was also related to faster driving and other crash-related conditions. Younger, less experienced, male drivers reported higher levels of aggressive expression. Abstract: This study tested the four factor structure of the Driving Anger Expression Inventory (DAX) in a sample of young Malaysian drivers and the relationship these factors had with several other variables. Confirmatory Factor Analysis broadly supported the four factor solution of the DAX, being: Personal Physical Aggressive Expression, Use of a Vehicle to Express Anger, Verbal Aggressive Expression and Adaptive/Constructive expression. The short version of the Driving Anger Scale was positively correlated with the three types of aggressive responses and not surprisingly with a variable comprised of all three types of aggressive responses (Total Aggressive Expression). Total Aggressive Expression was higher for males and negatively related to age, years licensed and slower preferred driving speed. All three of the aggressive forms of expression had significant relationships with crash-related conditions, such as: loss of concentration, losing control of their vehicle, having received a ticket and involvement in near-misses. In particular, all three of the aggressive forms of expression had significant relationships with losing control of the vehicle and Total Aggressive Expression was correlated with all crash-related conditions. In addition, Personal Physical Aggressive Expression and Total Aggressive Expression were both significantly related to crash involvement.